Prevalência da Chlamydia trachomatis pela técnica de reação em cadeia da polimerase (pcr) em mulheres inférteis - Approbato, Fabiana Carmo (2012)
The Chlamydia trachomatis is a common factor of sexually transmitted diseases. If not treated it can induce tubal obstruction, ectopic pregnancy and infertility. In adolescent women, the prevalence can reach 30%. When look for infertility treatment, the women are at older age, so they are at a different prevalence of Chlamydia. Objectives: To evaluate the prevalence of Chlamydia trachomatis by PCR, enzyme immunoassay or indirect immuno fluorescence at infertile patients. Methods: Design: Prevalence study. Diagnoses Test. Setting: Reproductive Laboratory (LABREP) - HC / UFG and Mater Clinic of Obstetrics and Gynecology, Goiânia, Brazil. Patients: One hundred and twenty patients attended from 2011 to 2012, from 20 to 48 years old. Main Outcome Measures: Age frequency histogram, exposition to pregnancy time, Chlamydia prevalence, Odds ratio for tubal obstruction, ectopic pregnancy and others STDs (Sexually Transmitted Diseases). It was calculate the age histogram frequency, and pregnancy exposition time. We used Chi Square statistical for Odds risk to tubal obstruction for serum positive patients; the Odds risk to ectopic pregnancy for serum positive patients and Odds risk to others STDs for serum positive patients. The rejection p was 5 % (p = 0.05). The Statistical Software used was BioEstat® and excel®. The study was submitted and approved by ethics committee of Clinical Hospital of Federal University of Goias State, Brazil. Results: The patients average age was 33.2 years, above of adolescent age prevalence, when chlamydia is frequently found. The average of exposition to pregnancy was 48.6 months. The PCR Chlamydia detection was less than 1 % (0.83 %). The Chlamydia PCR prevalence for serum positive was 2.4 % (one patient). We did not found Positive PCR between serum negative patients. The Odds to tubal obstruction for serum positive patients was 2.5. This was statistically significant. The Odds Ratio to ectopic pregnancy for serum positive patients was 1.31. This was not statistically significant. The Odds Ratio to others STDs for serum positive patients was 4.1 (p = 0.024). The Odds Ratio to ectopic pregnancy for tubal obstruction was 19.1. This was highly significant (p = 0.001). The NNT was 42. Conclusions: We conclude that C. trachomatis has a very low frequency at this population ( < 1 %), but heavy sequels of infection stays. The average age of the infertile patients was 33.2 years, above of the age mean of adolescents. We found association of positive serology screening and statistically significant risk for tubal obstruction, ectopic pregnancy and to others STDs.